2016
DOI: 10.1016/j.seizure.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of late remission in a cohort of Chinese patients with newly diagnosed epilepsy

Abstract: Patients with a high frequency of seizures prior to treatment or multiple seizure types may achieve late remission. Particular consideration should be given to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
15
2
Order By: Relevance
“…In contrast to our findings, previous studies reported a lower proportion of patients with no remission ranging from 15-30.9%. [7,11,15,18]. In general, despite the differences in the definition of the patterns, the current study found lower total remission (early and late) and a higher percentage of patients with no remission.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…In contrast to our findings, previous studies reported a lower proportion of patients with no remission ranging from 15-30.9%. [7,11,15,18]. In general, despite the differences in the definition of the patterns, the current study found lower total remission (early and late) and a higher percentage of patients with no remission.…”
Section: Discussioncontrasting
confidence: 68%
“…In a study conducted by Zhang et al in China, 80% seizure remission was observed [18]. Similarly, a slightly higher remission rate (69.1%) was reported by Shen et al [7]. On the other hand, seizure remission was reported as low as in 43.6% of patients in a study by Rizaldy et al [19].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…21,22 Previous literature on epilepsy have also suggested IEDs may predict unfavorable seizure outcomes and refractory epilepsy. 23,24 As for immunotherapy delay, one of the main causes was atypical and insidious symptoms, for example, symptomatic seizures occurred as the unique presentation in several patients with AIE, particularly in anti-LGI1 encephalitis. To date, there were fewer studies reporting the relationship between immunotherapy delay and the development of epilepsy in neuronal surface antibody-mediated autoimmune encephalitis.…”
Section: Discussionmentioning
confidence: 99%